Effect of water potential on imbibition, respiration and germination of leguminous Cratylia floribunda - Barrueto Cid, Luis Pedro; Oliva, Marco Antonio; Cardoso, António Américo (Pesquisa Agropecuaria Brasileira, 2014)
Green and brown seeds of the leguminous Cratylia floribunda, with and without scarification, were used to study the effect of decreasing water potential on their respiration, imbibition and germination. The water potential was determined in a solution of mannitol. It was also studied the effect of different levels of dehydration (induced in a dessicator with silica gel) and of rehydration on the respiration of scarified and imbibed green seeds of C. floribunda. In the non scarified green seeds, imbibition, respiratory activity and germination were not observed for any of the osmotic conditions used. Lower water potential affected the imbibition rate of the scarified green seeds. However it did not affect the final amount of water absorbed, respiration or the percent of germination. Concerning the respiration and the germination, it was concluded that the imbibition effect of mannitol is superior than the water potentials themselves. Germination was not detected with brown seeds. A problem of dormancy or internal damage is concluded for this case. The respiratory pattern of the scarified brown seeds was different from the scarified green seeds in spite of a similar imbibition. However, an accumulation of water for the highest potential and a depression effect of the lower potentials for the brown seed without scarification were observed, probably due to an inhibitory effect of mannitol. During the dehydration, the respiratory intensity variation was related to the remaining water content of the seed: high respiratory rates with low loss of water, and low respiratory rates with severe loss of water were observed. Related to the control, the variations of respiratory intensities were not markedly different from the rehydration. The high percentage of germination obtained after the rehydration suggests that dehydration had only a slight effect.